Matrix-dependent functional behavior of plant pectins in vegetable canned food systems - Laura Sengirbekova; Talgat Kulazhanov; Laila Syzdykova; Karlygash Abdiyeva; Gulnara Shambulova; Gulshat Zhaхylykova; Sanavar Azimova (Functional Foods in Health and Disease, 2026)
Background: Plant pectins are natural hydrocolloids and soluble dietary fibers whose technological and nutritional performance depends on interactions with proteins, lipids, starch, native cell- wall material, minerals, and phenolic compounds. Understanding this matrix dependence is essential for selecting an appropriate food vehicle for bioactive ingredients and for designing vegetable foods with predictable quality. Objective: To determine how pumpkin, zucchini, and apple pectins behave in liquid and structured vegetable canned- food matrices and to identify matrix- specific effects on antioxidant activity, fat content, dietary fiber, and microbiological quality. Methods: Pumpkin, zucchini, and apple pectins were incorporated into liquid pureed soups and structured vegetable–grain canned foods. Stage I compared botanical sources at 1. 1.0% (w/w); Stage II evaluated pumpkin pectin concentration (0. 5–1. 1.5%, w/w), processing temperature (80–95 ° C), and processing time (5–15 min). Antioxidant activity, fat, dietary fiber, and microbiological indicators were determined using standardized methods. Pearson correlation analysis and response surface methodology were used to examine matrix- specific process–structure–function relationships. Results: The effect of pectins depended on the food matrix. In soup- type products, antioxidant activity decreased after pectin incorporation, whereas in structured cereal- based systems it increased from 520.84. 84 to 685. 39 μmol TE 100 g⁻¹ in buckwheat- containing products and from 406.12. 12 to 426. 46 μmol TE 100 g⁻¹ in bulgur- containing products. Dietary fiber content increased from 2. 96 to 3. 11% in buckwheat- based products but decreased slightly from 3. 69 to 3. 39% in bulgur- based systems. The addition of pectins improved microbiological stability by reducing total microbial counts from 1. 1.6 × 10 ⁴ CFU g⁻¹ in control samples to